PENGARUH INOVASI PRODUK, PROMOSI, HARGA TERHADAP MINAT PEMBELIAN KOPI KENANGAN - Wijaya, Vernando; Krisna Marpaung, Fenny; Imelda Girsang, Christin (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study aims to analyze the influence of product innovation, promotion, and price on purchasing interest in Kopi Kenangan in Medan City. This study uses a quantitative approach with a sample of 100 respondents selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using validity tests, reliability tests, descriptive analysis, classical assumption tests, multiple linear regression analysis, t-tests, and F-tests. The results of the study indicate that product innovation has a positive and significant effect on purchasing interest, meaning that flavor variations, attractive packaging, and product updates can increase consumer interest. Promotion also has a positive and significant effect, where social media and digital campaigns have been shown to increase consumer awareness and purchasing interest. The price variable has a positive and significant effect on purchasing interest, indicating that price matching with product quality can increase consumer trust and decisions. Simultaneously, product innovation, promotion, and price have a significant effect on purchasing interest, with an Adjusted R² value of 0.815 or 81.5%, while the remaining 18.5% is influenced by other variables outside the study. The results of this study provide implications that the combination of attractive product innovation, effective promotional strategies, and appropriate pricing are important factors in increasing consumer purchasing interest in Kopi Kenangan products.